2015
DOI: 10.1097/mlr.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Evaluation of the Impact of Sex on Abdominal and Fracture Pain Care

Abstract: Background Previous studies examining gender-based disparities in Emergency Department (ED) pain-care have been limited to a single pain-condition, a single study-site, and lack rigorous control for confounders. Objective A multicenter evaluation of the effect of gender on abdominal pain (AP) and fracture (FP) pain-care outcomes. Research Design Retrospective cohort-review of ED visits at 5 US hospitals in January, April, July and October 2009. Subjects 6,931 patients with a final ED diagnosis of FP (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Women waited longer than men for administration of analgesia (16‐min difference, 95% CI 3.5 to 33 min), despite reporting similar pain scores 193 . This is consistent with retrospective reviews demonstrating that being a woman with abdominal pain is associated with a lower likelihood of receiving pain medication and delayed time to administration of pain medication when compared to men 194,195 . A large retrospective study utilizing national data found that minorities had a decreased OR of receiving opioids in the ED when compared to non‐Hispanic White patients, 0.50 for Black patients, and 0.85 for Hispanics 196 .…”
Section: Questionsupporting
confidence: 65%
See 1 more Smart Citation
“…Women waited longer than men for administration of analgesia (16‐min difference, 95% CI 3.5 to 33 min), despite reporting similar pain scores 193 . This is consistent with retrospective reviews demonstrating that being a woman with abdominal pain is associated with a lower likelihood of receiving pain medication and delayed time to administration of pain medication when compared to men 194,195 . A large retrospective study utilizing national data found that minorities had a decreased OR of receiving opioids in the ED when compared to non‐Hispanic White patients, 0.50 for Black patients, and 0.85 for Hispanics 196 .…”
Section: Questionsupporting
confidence: 65%
“…193 This is consistent with retrospective reviews demonstrating that being a woman with abdominal pain is associated a lower likelihood of receiving pain medication and delayed time to administration of pain medication when compared to men. 194,195 A large retrospective study utilizing national data found that minorities had a decreased OR of receiving opioids in the ED when compared to non-Hispanic White patients, 0.50 for Black patients, and 0.85 for Hispanics. 196 While advocating for equity in analgesia, the writing group also recognized that medically appropriate differences in analgesia approaches may be warranted, based on factors such as pain mechanisms and adverse effects unique to individual patients (e.g., avoidance of NSAIDs in patients with advanced renal disease or gastrointestinal bleeding) or patient groups (e.g., use of Beers list to guide medication selection in older adults).…”
Section: Pharmacologic Analgesia (Nonopioids and Opioids)mentioning
confidence: 99%
“… 2 These biases appear to affect treatment recommendations, as male patients are less likely to receive psychosocial assessment or treatment for pain 3 , 4 and women patients are less likely to receive more aggressive analgesic treatment. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…In a study from the University of Pennsylvania, women were 13%-25% less likely to receive opioid analgesia for abdominal pain and waited longer for any form of analgesia than male patients. 10 Siddiqui et al 9 showed that women with abdominal pain were less likely to receive analgesia within the first 180 minutes of a visit (OR = 0.91, 95% CI, 0.84-0.97) as compared to men, but there was no such sex discrepancy for patients with fracture pain, 9 and there is still further literature that does not show any difference for female as compared to male patients. 2,7 We do not know of any studies that have examined sex-based disparities in analgesic administration among pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found significant disparities in treatment among races/ ethnicities, although to different degrees and in different specific contexts. [2][3][4][5][6][7][8] Likewise, there is some evidence that adult females receive more analgesics for acute pain than males, 3,8 but there is also evidence that they receive either fewer 9,10 or equal 2,7 amounts of analgesics.…”
mentioning
confidence: 99%